2019
DOI: 10.1039/c8cp06967k
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing the plasma formed during acoustic cavitation in [BEPip][NTf2] ionic liquid

Abstract: What do rovibronic temperatures tell us? Example of the sonolysis of [BePip][NTf2] ionic liquid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…They observed for [C 8 mpyrr][NTf 2 ] that increasing the sonication time led to a decrease in the intensities of the SL continuum and lines. This decrease was attributed by Pflieger et al [10] to the progressive poisoning of the plasma inside the bubbles by the sonolysis degradation products. This latter work presented the time evolution with a one-minute resolution of SL spectra of a very dry [BEPip][NTf 2 ] ionic liquid (Figure 1) under Ar and underlined that degradation of the IL had already started in the first minute of sonication.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…They observed for [C 8 mpyrr][NTf 2 ] that increasing the sonication time led to a decrease in the intensities of the SL continuum and lines. This decrease was attributed by Pflieger et al [10] to the progressive poisoning of the plasma inside the bubbles by the sonolysis degradation products. This latter work presented the time evolution with a one-minute resolution of SL spectra of a very dry [BEPip][NTf 2 ] ionic liquid (Figure 1) under Ar and underlined that degradation of the IL had already started in the first minute of sonication.…”
Section: Introductionmentioning
confidence: 85%
“…The IL [BEPip][NTf 2 ] was prepared and characterized as described previously [10]. It was then used in its water saturated form or dried under a vacuum and stirred at 80 • C for one and a half days to keep the water content as low as possible.…”
Section: Methodsmentioning
confidence: 99%
“…Didenko et al [56] estimated T max of about 15,000 K in a moving single bubble case and suggested that the T max reached could be 30,000 K in stable single bubble systems. Pflieger et al [57] used molecular emissions observed in an ionic liquid and estimated rotational and vibrational temperatures in the range 4000–6000 K.…”
Section: Experimental Considerationsmentioning
confidence: 99%
“…From the spectra of MBSL, various information on the physical and chemical nature of the bubble interior can be obtained such as the bubble temperature and pressure, chemical species present inside a bubble, etc. [ 7 , 8 , 46 , 55 , 98 , 99 , 100 , 101 , 102 , 103 ]…”
Section: Applications Of Mbslmentioning
confidence: 99%